Distribution of Ornamental Aquatic Plants in the Polonnaruwa District - Corea, A.S.L.E. (NARA, Sri Lanka, 2003)
Ornamental aquatic plants have drawn much attention of the aquarium fish exporters in the past few years. Although the export of ornamental aquatic plants has a capacity to expand, low production has become a limiting factor. Many species are still being collected from the wild for export even though the regulations permit only the export of propagated stocks. Strictly restricted species which include the endemic species and globally threatened species are propagated to some extent while the major part of other locally available species find their to the export market directly from the wild. In Sri Lanka, however, the actual status of the distribution of ornamental aquatic plants and their availability in the natural habitats has not been documented properly. This gives rise to many problems in granting permission to export of the wild collected plants, especially as the exporters demand the right to export plants collected from the wild indicating that they are abundant in the natural habitats. Present study was therefore carried out to investigate the distribution of the aquatic plants in the natural habitats in the Polonnaruwa district. A total of 44 species were recorded during the survey from 345 seasonal tanks, 11 villus, 72 perennial reservoirs, 122 sampling points in irrigation canals and 87 sampling points in streams. These included 4 globally threatened species, 2 endemic species both belonging to the genus Cryptocoryne and 6 species of common aquatic weeds. The two endemic species are listed as threatened species. The distribution of these endemic species were limited to irrigation canals and streams while the other threatened species were found in seasonal tanks. The major threats to the endemics identified during the survey were sand mining, habitat deterioration and collection for commercial purposes. Fast spreading of aquatic weeds also created a problem in irrigational canals and seasonal tanks.